2002
DOI: 10.1016/s0168-8278(01)00279-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin directly disrupts membrane lipid polarity and fluidity, protein order, and redox status in rat mitochondria

Abstract: Background/Aims: Unconjugated bilirubin (UCB) impairs crucial aspects of cell function and induces apoptosis in primary cultured neurones. While mechanisms of cytotoxicity begin to unfold, mitochondria appear as potential primary targets.Methods: We used electron paramagnetic resonance spectroscopy analysis of isolated rat mitochondria to test the hypothesis that UCB physically interacts with mitochondria to induce structural membrane perturbation, leading to increased permeability, and subsequent release of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 45 publications
(53 reference statements)
5
56
1
Order By: Relevance
“…That bilirubin is capable of directly causing depolarization of isolated mitochondria, as has previously been proposed by Rodrigues et al, 64 is supported by our light-scattering and rhodamine fluorescence data. Our finding that bilirubin-induced large-amplitude swelling is not blocked by cyclosporin A, an established inhibitor of the mitochondrial PTP, 58,77 in conjunction with data from Rodrigues et al indicating that bilirubin alters mitochondrial lipid polarity, 23,78 further suggests that bilirubin is capable of exerting a direct effect on mitochondrial membrane integrity.…”
Section: Effect Of Bilirubin On the Permeability Of Isolated Mitochonsupporting
confidence: 76%
“…That bilirubin is capable of directly causing depolarization of isolated mitochondria, as has previously been proposed by Rodrigues et al, 64 is supported by our light-scattering and rhodamine fluorescence data. Our finding that bilirubin-induced large-amplitude swelling is not blocked by cyclosporin A, an established inhibitor of the mitochondrial PTP, 58,77 in conjunction with data from Rodrigues et al indicating that bilirubin alters mitochondrial lipid polarity, 23,78 further suggests that bilirubin is capable of exerting a direct effect on mitochondrial membrane integrity.…”
Section: Effect Of Bilirubin On the Permeability Of Isolated Mitochonsupporting
confidence: 76%
“…BR causes mitochondrial dysfunction with collapse of inner mitochondrial membrane potential, a diminished activity of cytochrome c oxidase, and the release of cytochrome c to the cytosol, which is an initiation of apoptosis via mitochondrial intrinsic pathway (Rodrigues et al, 2002;Ostrow et al, 2004;Brites and Brito, 2012). BR may also induce apoptosis via mitochondrial extrinsic pathway by activation of caspase-8, suggesting that BR interaction with a death receptors (e.g.…”
Section: Bilirubin Toxicitymentioning
confidence: 99%
“…Many reports have shown BR disrupts the functions of mitochondria at the membrane level and also induce apoptosis via both intrinsic and extrinsic apoptotic pathway (Rodrigues et al, 2002;Seubert et al, 2002;Ostrow et al, 2004;Vaz et al, 2011;Brites and Brito, 2012). BR has been also reported to induce expression of regulatory genes and proteins for unfolded protein response (UPR), which is a key regulatory defense mechanism against ER stress (Calligaris et al, 2009;Oakes and Bend, 2010).…”
mentioning
confidence: 99%
“…UCB increased lipid polarity and fluidity, as well as protein mobility, resulting in an increased permeability of this membrane and release of cytochrome c (Rodrigues et al, 2002b,c). Ursodeoxycholic acid, a mitochondrial membrane-stabilizing agent that prevents the changes in mitochondrial transmembrane potential, almost completely abolished the UCB-induced membrane perturbation in isolated mitochondria (Rodrigues et al, 2002b) and inhibited the UCB-mediated apoptosis of neurons and astrocytes (Silva et al, 2001). Rodrigues et al (2002d) reported that the apoptotic effect of UCB in primary cultures of rat neurons and astrocytes decreases as a function of age-in-culture of these cells, thus confirming the earlier findings of Amit and Brenner (1993) in primary cultures of fetal rat glial cells.…”
mentioning
confidence: 98%